Tu não te moves de ti? sobre o bruto encontro com o envelhecimento - Vidal, Thales Miguel Gaspar (2017)
The general purpose of this study is to carry out an interpretation of the film narrative of Olivier Assayas’s Clouds of Sils Maria, 2014, to discuss the potentiality of a conceptual articulation between the fields of Psychoanalysis, Gerontology and Arts in order to address the aging process from both subjective and social points of view. The specific objectives outlined are: 1) to reflect upon “the contribution of cinema to dealing with existential, social and political themes” (ROSA apud DUNKER & RODRIGUES, 2015, p. 12), and thereby highlight the function of fiction in the difficult and daily task of reinventing oneself; 2) to identify, in the analysis of the film, how it translates an enquiry and an answer about what aging is. From this perspective, to determine the elements of confrontation and defenses brought into play to question the spectator about this process and its double translation: subjective and social; 3) to problematize the alienating face implied in the adoption of the chronological criterion as a marker of entry into old age; 4) to contribute to the strengthening of an interdisciplinary perspective on the studies about the human aging. This work is justified as it seeks to address the issue posed by Messy (1999, p.14): "when does one get old outside of the social repertoire?". He does so by referring the focus of the reflection to the film protagonist’s drama, a 40-year-old woman who suddenly sees herself as old because someone else has offered her that image. In this drama, her defenses against the identification with the stigmatizing social images associated with old age are heavily featured. The methodology used was the interpretation of the film narrative taking concepts deployed in a bibliographic review that articulated the aforementioned fields as reading operators. As a result, the subjective effect produced by the brutal (MESSY, 1999) encounter with aging itself was identified and discussed, a position avoided by the protagonist of the film in question, who has always attributed a range of negative characteristics to old age, as if these were strange to her. From such reflection, I could conclude that there is a remarkable complexity in the subjective process of aging which is substantially increased in the excessively narcissistic contemporary societies